PERSONALITY AND PROFESSIONAL TRAITS: HOW INTERPERSONAL CHARACTERISTICS DEFINE SOCIAL WORKERS - Alina COSTIN (Association of Social and Educational Innovation, 2024)
It is considered that self-awareness is a fundamental element in personal and professional development, especially in social assistance, where constant contact with the other implies self-discovery, self-knowledge, reflection, change (Alicke, Zhang, Stephenson, 2020). In this context of the need for self-knowledge and understanding, the objective of this paper is to highlight the existing differences according to gender and self-acceptance in terms of interpersonal characteristics developed early in the family: "Feeling of social communion - prosocial", "Agreement - compliance", "Taking the lead - leader", "Desire for recognition - approval" and "Being on guard - caution", dimensions measured with the BASIS-A questionnaire. A series of demanding and transversal skills are the prerogative of this profession, among which, conflict management, leading and mediating relationships, compassion, agility, assertive approach, etc. It is necessary to create contexts for evaluating the interpersonal traits of social workers and highlighting the interpersonal styles within the broad framework of the global evaluation of their personality. In this sense, we used the BASIS Questionnaire (Unconditional Self-Acceptance Questionnaire - USAQ) and the Unconditional Self-Acceptance Questionnaire. The results indicate differences regarding gender and unconditional acceptance on the dimensions of feeling of social communion, leadership quality, recognition, approval.